The celestial cycle the theme of Paradise lost in world literature with translations of the major analogues. - Kirkconnell, Watson, 1895-1977 (Heritage., 1952)
An anthology of translated analogues, in whole or in part, on the theme of paradise lost. It is an indispensable resource for any serious student or scholar of Milton's Paradise Lost.